Information visualization in the era of innovative journalism - Toural-Bran, Carlos (London ; New York : Routledge, 2020)
"Information Visualization in The Era of Journalistic Innovation brings together over thirty authors from countries around the world to synthesize how recent technological innovations have impacted the development, practice, and consumption of contemporary journalism. As technology rapidly progresses, shifts, and innovates, there have been immense changes in the way we communicate. This book collects research from around the world that takes an in-depth look at the primary transformations related to journalistic innovation in recent times. High profile contributors provide cutting-edge scholarship on innovation in journalism as it relates to emergent topics such as virtual reality, podcasting, multimedia infographics, social media, mobile storytelling, and others. The book pays special attention to the development of information visualization and the ability of recent innovations to meet audience needs and desires. Students and scholars studying contemporary journalism history and practice will find this a vital and up-to-date resource, as well as those studying communication technology as it relates to marketing, PR, or mass media broadly"--
OCLC-licensed vendor bibliographic record.
Keywords: Journalism -- Technological innovations; Immersive journalism; Online journalism; Information visualization; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Journalism; PHOTOGRAPHY / Photojournalism